Effects of Peppermint Lotion on Pain Intensity and Cortisol Levels in Adolescents with Primary Dysmenorrhea - Meliya, Leza Fica; Sumarni, Sri; Susanto, Edy (Indonesian Journal of Global Health Research, 2024)
Dysmenorrhea is an important topic in reproductive health, especially in adolescents because it has a major impact on the quality of life of adolescents. Dysmenorrhea in adolescents negatively affects physical activity, school attendance, concentration during lessons and academic performance. Some of the symptoms that adolescents often experience in dysmenorrhea include headaches, back pain, fatigue, anxiety and other physical and psychological complaints. Pharmacological treatments commonly used often cause dangerous side effects so alternative treatments are needed that are considered safer and more effective. Peppermint is an example of a nonpharmacological therapy that aims to provide a distraction and relaxation effect of the body by stimulating the body to release endorphine compounds which are pain relievers so as to create feelings of comfort, calm nerves, and stabilize blood pressure. Objective: This study aims to analyze the effect of Peppermint lotion administration on pain intensity and cortisol levels in adolescents with primary dysmenorrhea. Method: This study is a true experiment with randomized pretest-posttest with control group. The number of samples in the study was 40 adolescent respondents with primary dysmenorrhea according to inclusion criteria divided into 20 people in the intervention group who were given 3% peppermint lotion with a frequency of administration 3 times a day for 3 days and 20 people in the control group given placebo lotion. Measurement of pain intensity using the Numeric Rating Scale (NRS) and cortisol levels using blood serum performed on the first day (pretest) and third day of menstruation (posttest). Data analysis using independent t test and mann whitney. Results: In the intervention group given peppermint lotion there was an average decrease in pain intensity of 4.6 while the control group was 3.55 with effect size 0.867 and p value = 0.013. The average decrease in cortisol levels in the intervention group was 2.64 μg/dL and the control group was 0.94 μg/dL with effect size 0.864 and p value = 0.010. Conclusions: Administration of peppermint lotion for 3 days has an effect on reducing pain intensity and cortisol levels in adolescents with primary dysmenorrhea.